Press freedom, a sine qua non for good governance? Nigeria experience (2010)
Within the context of the frequency of its occurrence in recent times, it is not out of place to observe that the expression “good governance” is beginning to take on a conceptual character. Although it could defy a straightforward meaning, like the proverbial elephant however, it is easy to identify. Guobadia, D.A (2000). The Legislature and good governance under the 1999 Constitution, 43. Concepts have their ways of emerging in a people’s consciousness and, taken as one, the notion of good governance in contemporary Nigeria has, no doubt been conditioned by the vagaries and vicissitudes of our national life. The geo-political entity called ‘Nigeria’ has over the years, precisely since the nation’s independence been groping for panacea to the socio-economic problems facing her. The successive governments for the past 50 years since Nigeria’s independence have, in their attempt to bring succour to their subjects, appears to have plunged the nation into abyss of poverty and despondency. This unpleasant situation Nigeria has found herself among the comity of nations is a major concern, not only for the government but also the governed who bear the brunt of the consequences of the action or inaction of the former. In 1960, Nigeria gained independence with pomp and pageantry, great hope and expectations which ushered her into the 1st Republic.